Epistemology of Power: Ontology Matters - Nelson, Reba (My University, 2010)
This paper explores the implications of an epistemology of power for family therapists. It begins by explicating the complementary relationship between ontology and epistemology Next, logical typing and levels of abstraction are explicated as a means of understanding how power is reified and confused with power as a metaphor. Given that discussions of power and family violence often become entwined, the paper then moves to the implications of an ecosystemic epistemology in the treatment of violence. An alternative to the metaphor of power is offered. The paper concludes with a discussion of whether family therapists have abandoned a relational view of power in favor of seeking how to most effectively claim and wield power
Keywords: Epistemology; Ontology